Dinâmicas territoriais e métricas espaciais: avaliação de expansão urbana em cidade de porte médio - Menzori, Ivan Damasco (2021)
The rapid urban population growth was accompanied by intense expansion processes in urban areas, especially in cities developing countries. The confrontation of the challenges emerging from these processes motivated several processes and regulatory acts concerning a more sustainable urban development in which, specifically in Brazil, the legal and philosophical basis of spatial planning is largely related to the social function of property at the local level of cities, through master plans. As an instrument of urban environmental management, usually present in the master plans, zoning plans allow the definition of a city's functions through special zones (or areas) of environmental protection (with restricted or conditioned land use/cover), of residential, mixed, commercial and industrial uses, as well as their degrees of land parcel and density. However, even when environmental preservation and recovery zones are foreseen, as well as other aspects related to the physical environment that may be impacted by extensive urbanization, master plans seem ineffective in these aspects when addressed by the local authorities. As a rule, peripheral and extensive urbanization is related, among other factors, to public policies that favour economic growth at the local level, to the detriment of regulating urban expansion. In this context, analyses of the implementation of master plans, their physical-territorial results, and their relationship with territorial governance are still scarce. In this study, the role of territorial governance in master plans implementation practices is evaluated, as well as the geospatial results of urban growth in a medium-sized Brazilian city (Araraquara-SP) are explored, in an analytical way with quantitative empirical approaches. The objective is to identify possible discrepancies and patterns (different from randomness) in the geospatial results of urban growth, according to different periods of territorial governance, assuming that governance capacity affects the spatial distribution of urban growth and the regulation of urban expansion. The results show different patterns of urban growth associated with different political-administrative terms in office, even when implementing the same master plan, suggesting that these results may have been shaped by either the application or the abstention of the regulatory planning framework, with different degrees of permissiveness towards peripheral and extensive urbanization processes, to the detriment of extreme environmental criticality areas and the precepts of a more sustainable urban development.